Understanding Service-Oriented Architecture (SOA): A systematic literature review and directions for further investigation - Niknejad, N; Ismail, W; Ghani, I; Nazari, B; Bahari, M; Hussin, AB (Pergamon-Elsevier Science Ltd, 2024)
Indexed by Scopus